Exploited for a Good Cause? Campaigning Against Unpaid Internships in the UK Charity Sector - Vera Weghmann (tripleC: Communication, Capitalism & Critique, 2015)
In this activist report I aim to show that unpaid internships in charities need to be understood as both morally unjust and exploitative, and that we can do something about it. Together with my fellow interns and interns from another charity, I organized a campaign, NoPay?NoWay!, for a decent wage for all workers in the charity sector, including interns. After six months, we successfully managed to stop the use of unpaid internships in both workplaces. This is my story.